2014
DOI: 10.5194/isprsarchives-xl-1-293-2014
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effects of Spatial Resolution for Small Landslide Susceptibility and Hazard Mapping

Abstract: Commission I, WG I/2 KEY WORDS: LiDAR, landslide, feature, extraction, spatial, resolution, DEM ABSTRACT:Spatial resolution plays an important role in remote sensing technology as it defines the smallest scale at which surface features may be extracted, identified, and mapped. Remote sensing technology has become a vital component in recent developments for landslide susceptibility mapping. The spatial resolution is essential, especially when landslides are small and the dimensions of slope failures vary. If t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Similar results were demonstrated by Hengl (2006), Paudel et al (2016), Tarolli and Tarboton (2006), Penna et al (2014) and Mora et al (2014). Based on achieved results, it can be determined that selected spatial resolution of DEM depends mostly on objective of the study and used methodology.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Similar results were demonstrated by Hengl (2006), Paudel et al (2016), Tarolli and Tarboton (2006), Penna et al (2014) and Mora et al (2014). Based on achieved results, it can be determined that selected spatial resolution of DEM depends mostly on objective of the study and used methodology.…”
Section: Discussionsupporting
confidence: 73%
“…On the contrary landslide susceptibility mapping does not require such high resolution of DEM (Pawłuszek and Borkowski, 2016, Pawłuszek and Borkowski, 2017, Mora et al, 2014. Some studies demonstrated that choosing the finest DEM resolution is not always the best choice (Mora et al, 2014, Tarolli and Tarboton, 2006, Penna et al, 2014. Thus, it is an open question, if small divergences in micro-topography scale, which are represented in DEM of a fine resolution increase the performance of landslide mapping process.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations